Global Heritage Stone: Estremoz Marbles, Portugal - Lopes, Luís (2014)
Abstract: Paleozoic calcitic marbles are found in the Estremoz Anticline, Ossa-Morena Zone (Southern Branch of the European Variscides in Portugal). This 40 km NW – SE structure presents outcrop continuity and intense mining activity since the Roman Period. The structure has a Precambrian core and the younger rocks are from the Devonian Period. The marbles occupy an intermediate stratigraphic position in the Cambrian age Volcano Sedimentary Sequence. The Variscan Orogeny had two pulses with different intensities under ductile and brittle tension fields. The Alpine Cycle also caused more fracturing of the marbles. The geological features imprinted in the marbles are beautiful aesthetic patterns highlighted when used as dimension stone. Since the Roman period, pieces of art made with Estremoz Marble were exported abroad and can be found in museums and archaeological sites throughout Europe and North Africa countries. Present day, Estremoz Marble objects can be found all over the world. The very rich marble based heritage is omnipresent in cities, and the countryside is marked by intense mining activity side by side with rural industries; therefore the region has unique characteristics allowing the development of integrated industrial tourism routes, promoting sustainable development of industrial, scientific and technological cultural opportunities. The historical and widespread application of these marbles in national and international monuments, some of them already part of the UNESCO World Heritage Sites, is a condition to propose them as Global Heritage Stone Resource for their international recognition.